Effects of exposure to Diazinon on the lung and small intestine of Guinea pig, histological and some histochemical changes - Rady,Mohamed Ibrahim (2009)
The present study aimed to evaluate the histological changes and adverse effects on the total protein and general carbohydrates in the lung and small intestine of guinea pig "Cavia porcellus" induced by the exposure to sub lethal doses of the organophosphate insecticide diazinon. Primarily, diazinon insecticide oral LD50 was investigated after administrating orally different doses in guinea pig and was determined as 213 mg/Kg bw., the animals exposed to sub lethal doses of this insecticide revealed histological changes in both lung and intestine in a dose dependent manner. Also, significant decrease in the total protein and general carbohydrates in the lung and intestine were mostly observed, especially with the higher doses of the insecticide in comparison with control group.